[PP.16.26] CLINICAL FEATURES OF 'THERMOSENSITIVE HYPERTENSION' - THE REAL BP STUDY. (September 2017) - Imaizumi, Y.; Kaihara, T.; Eguchi, K.; Yamamoto, M.; Kaku, R.; Kario, K.
Abstract : Objective: Temperature is a well-known factor of blood pressure (BP) variation. It is not yet established which type of hypertensives well respond to the temperature change. We tested the hypothesis that there is a phenotype of hypertensives whose home BP shows exaggerate changes by surrounding temperature variations. Design and method: We studied 220 hypertensives in the Real BP study, a hospital-based, observational study of home BP telemonitoring system. Home systolic BP (HSBP) and accompanying in-door temperature are evaluated using the telemonitoring home BP monitor (HEM-7252G), in the morning (just after waking up) and at night (before going to bed) for seven consecutive days, three times per each occasion. The BP values were defined as the means of the three BP readings in each occasion. Brachial-ankle pulse wave velocity (baPWV) and maximum carotid intima-media thickness (max-IMT) are also evaluated at the time of the study entry. Results: In all subjects, we performed mixed model analysis for HSBP. The in-door temperature was negatively associated with HSBP (Estimates: -0.98, Standard error: 0.08, p < 0.001) even after adjusting for age, sex, BMI, clinic SBP, current smoking, current drinking, and the time of bathing/week (Table). In each subject, we calculated the correlation coefficient for in-door temperature and HSBP, and 67 subjects (30.1%) showed significant negative correlation [thermosensitive group (TS)]. In the TS group, the presence of COPD (p < 0.05) and max-IMT tended to be higher (p = 0.05) than the others. However, there was no significant difference in baPWV between the groups. Then we performed multivariable logistic regression analysis for the top 25 percentile [Quartile (Q) 4 vs. Q1–3] of the correlation coefficient between in-door temperature and HSBP as the dependent variable. As a result, those with higher max-IMT tended to be associated with Q4 (Odds ratio: 2.00, 95% CI, 0.96–3.92; p = 0.067). Conclusions: In-door temperature was significantly associated with HSBP, and this association was strong in COPD and those with higher max-IMT. Thus, those phenotypes of hypertensives may be 'thermosensitive hypertension'. Cold temperature would be a trigger for cardiovascular events in those subjects. Figure. No caption available.